Enhancement of gaseous BTEX adsorption on RH-MCM-41 by chlorosilanes - Areerob, T.; Chiarakorn, S.; Grisdanurak, N. (Universiti Kebangsaan Malaysia, 2015)
In this research, the surface hydrophobicity of a mesoporous molecular sieve synthesized from rice husk silica, called RH-MCM41 was improved via silylation techniqueto enhance the adsorption efficiency of non-polar volatile organic compound. The effect of chlorosilane leaving on was analyzed with three silanes containing different numbers of chloride leaving group; trimethylchlorosilane (TMCS), dimethyldichlorosilane (DMDCS) and methyltrichlorosilane (MTCS). The unmodified RH-MCM-41 was soaked in 100 mL of 5% v/v of silane reagent at 30ºC for 24 h. The results showed that the silane loading on the RH-MCM-41 was in the order of increasing number of leaving groups as MTCS > DMDCS > TMCS. The crystallinity results studied by X-ray diffractometry indicated that the silylation did not affect the hexagonal pattern of RH-MCM-41. However, the porosity of the silylated RH-MCM-41 was significantly decreased after silylation, especially by MTCS, due to pore blocking. After silylation, the adsorption performance of gaseous BTEX (benzene, toluene, ethylbenzene and xylene) on the silylated RH-MCM-41 was determined by gas chromatography equipped with flame ionization detector (GC-FID). From the results of humidity effect on adsorbability, the BTEX adsorption capacity of the unsilylated RH-MCM-41 was dropped a half, conversely the BTEX adsorption capacity of all silylated RH-MCM-41 was decreased in range of 20-30% when the relative humidity increased from 25 to 99%. This was indicated that the influence of humidity on the BTEX adsorption was relieved after silylation. In additions, the maximum BTEX adsorption capacity belonged to RH-MCM-41 silylated by TMCS which was recommended for the enhancement of non-polar volatile organic compounds adsorption.